Price Level Determination in a Heterogeneous Monetary Union - Paul Bergin (University of California, Department of Economics, 1997)
A monetary union requires that a common central bank be shared among multiple nations, where governments and households may well be heterogeneous across national borders. A dynamic stochastic general equilibrium model of a two-country monetary union provides a natural setting in which to examine the implications of agent heterogeneity in government fiscal policies can be accommodated within a monetary union. Second, household heterogeneity gives monetary policy a reallocative dimension which affects price-level determination. For example, dissimilar preferences for holding money tend to enhance the potency of a monetary contraction to lower inflation. Fiscal federalism may reverse this effect.
Keywords: 330